Vertical force production in soccer: Mechanical aspects and applied training strategies. - Loturco, I.; Bishop, C.; Freitas, T. T.; Pereira, L. A.; Jeffreys, I. (Strength and Conditioning Journal, 2020)
Vertical force production (VFP) is widely recognized as a critical determinant of performance in a series of soccer-specific activities, such as sprinting, jumping, and changing direction. Therefore, practitioners are constantly seeking better and more effective strategies to improve VFP in professional soccer players. This article analyzes the mechanical aspects associated with the actual role played by VFP in elite soccer, and also examines and highlights the training considerations related to its appropriate and effective development during modern soccer seasons.